Economic Impact of a Bluetongue Serotype 8 Epidemic in Germany - Gethmann, Jörn; Probst, Carolina; Conraths, Franz J. (Frontiers in Veterinary Science, 2020)
Background and objectives Germany was affected by Bluetongue virus serotype 8 (BTV-8) from 2006 to 2009 and recorded new cases since December 2018. We assessed the economic impact of the epidemic from the first cases in 2006 until 2018. Direct costs include production losses, animal deaths, and veterinary treatment. Indirect costs include surveillance, additional measures for animal export, disease control (preventive vaccination and treatment with insecticides), vector monitoring, and administration. Methodology To estimate the financial impact of BTV-8 on different species and production types at the animal level, we performed a gross margin analysis (GMA) for dairy and beef cattle, and sheep. To estimate the impact on the national level, we used a modified framework described by Rushton et al. (1999) and applied a methodology described by Bennett (2003). Both the GMA and the economic model on national level were implemented in Excel and the Excel Add-in @Risk. The tools, which are widely applicable, also for other diseases, are made available here. Results The financial impact of a BTV-8 infection at the animal level was estimated at 119-136 Euros in dairy cattle, at 27 Euros in beef cattle, and at 74 Euros in sheep. At the national level, the impact of the BTV-8 epidemic ranged between 157 and 203 million Euros (mean 180 million Euros). This figure consisted of 132 (73 %) and 48 (27 %) million Euros for indirect and direct costs. Indirect costs included 89 million Euros (67 %) for vaccination, 18 million Euros (14 %) for insecticide treatment, 15 million Euros (11 %) for diagnostic testing of animals dispatched for trade, 8 million Euros (6 %) for monitoring and surveillance, and 3 million Euros (2 %) for administration. The highest costs were induced by a compulsory vaccination campaign in 2008 (51 million Euros; 28 % of the total costs) and the disease impact on cattle in 2007 (30 million Euros; 17 %). Discussion We compare the outcome of our study with economic analyses of Bluetongue disease in other countries, discuss the suitability of GMA and the developed tools for a wider application in veterinary economics.